2009
DOI: 10.1159/000236525
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Perceived Health Status Among Caregivers of Stroke Patients

Abstract: Objective: To identify the main determinants of burden and perceived health status in caregivers of Brazilian stroke survivors. Methods: Cross-sectional study. Caregivers answered the Hospital Anxiety and Depression Scale (HADS), Zarit caregiver burden interview (ZCBI) and EuroQol. Patients were assessed with the National Institute of Health Stroke Scale, Barthel index (BI), modified-Rankin scale (m-RS), Mini Mental State Examination and HADS. Results: 200 caregiver-patient dyads were assessed. Caregivers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
45
4
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 63 publications
10
45
4
6
Order By: Relevance
“…In addition to this, the unemployment status and low income levels would have been a significant barrier to the majority of the caregivers in this study being able to employ other full-time care providers. This distribution was similar to that reported by other researchers who also found that the largest percentage of caregivers was females and spouses (5,14,15).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition to this, the unemployment status and low income levels would have been a significant barrier to the majority of the caregivers in this study being able to employ other full-time care providers. This distribution was similar to that reported by other researchers who also found that the largest percentage of caregivers was females and spouses (5,14,15).…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were reported in a Brazilian population (14). The majority of caregivers were females who were significantly younger than the stroke patients and had more years of formal education.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, in a study conducted by Mollaoglu et al (6) significantly high scale scores were observed on the part of caregivers whose patients are dependent according to the BI and who meet all patients' needs. Parallel to the results of our study, Carod-Artal et al (37) indicated a negative relationship between the functional status of stroke patient caregivers and caregiver burden.…”
Section: Discussionsupporting
confidence: 90%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The impact of cerebrovascular diseases matters not only because of the burden of death [1][2][3][4][5][6][7][8] and the costs of hospitalizations, 9 but also because of the late effects from the disease, such as the degree of motor disabilities, post-stroke depression, reduced cognitive function and, consequently, the reduced quality of life among stroke survivors and their caregivers. [10][11][12] However, mortality data has a natural limitation; classical prevalence surveys 13 are relatively expensive; and incidence-based population studies [14][15][16] are only suitable for small and middle-size towns. Recently, in parallel with cross-sectional studies using the traditional multistage cluster approach, new technologies for gauging the frequencies of diseases and disabilities have emerged, such as telephone surveys 17 and household inquiries conducted by community health workers within primary care settings.…”
Section: Introductionmentioning
confidence: 99%